PUBLIC ADMINISTRATION PERFORMANCE: NEW EUROPEANUNION MEMBER STATES - Немец, Юрай (Public Administration Issues, 2023)
Measuring the performance of public administration systems represents a typical “wicked problem”, as it involves a  number of complex implementation  issues. However,  even in the current period, when the ideology of New Public Management is dead for most experts, the European Union, international organizations and think tanks are trying to measure and compare the performance of public administration systems of countries. This paper summarizes the  main initiatives of the European Union in this field and tries in its main part to  review the situation of the new European Union member states from Central and Eastern Europe. Qualitative secondary analysis of data and simple statistics are the main methods of this paper, which is an original contribution to its general  topic. The findings show that the main tools used by the European Union to measure and manage the performance of public administration  in the member and candidate countries are the European Semester, the recent EUPACK project, the standards developed by SIGMA OECD for the candidate countries and various statistical surveys. The data obtained   show that the  performance of public  administrations in the new EU Member States from the CEE region  varies widely, with most of them being “followers”. The reasons for such large differences in performance should be the subject of  further research.